„Zataję siebie w kropce tego wiersza” – językowe precjoza w poezji Urszuli Kozioł - Skibski, Krzysztof (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The article concerns textual phenomena in the poetry of Urszula Kozioł, which constitute a part of a linguistic method for examining relations between elements of poetic language. The examples discussed concern free verse – they reveal elaborate structures and linguistic processes focused on syntactic condensation, poetic accommodation, elliptic verse or phraseological trace. In the poetry of Kozioł, especially phraseology is original, which makes the receptive perspective adopted at describing linguistic phenomena representative of complicated formal-semantic processes. The draft is an attempt to read the Poet’s texts with the use of linguistic tools, so it not only gives a complete picture of an individualised poet but helps to point out peculiarities, the examination of which requires a reflection on language perception in poetic structures.